Peran Pendidikan Agama Islam Dalam Meningkatkan Nilai-Nilai Moral Keislaman Di Era Digitalisasi Pada Lingkungan SMP Swasta Plus An-Nur Mulia Kota Tebing Tinggi - Safitri, Ridzki Aidila; Nasution, Herry Syahbannuddin; Syahlan, Ali (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This study aims to examine the role of Islamic Religious Education (PAI) in enhancing Islamic moral values in the digitalization era within the environment of SMP Swasta Plus An-Nur Mulia in Tebing Tinggi City. The rapid development of digital technology presents new challenges for educators, including PAI teachers. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The findings of the study indicate that digitalization has brought positive impacts on PAI learning through broader access to information, but it also presents challenges, such as the spread of negative content. PAI plays a crucial role in guiding students to use technology wisely while instilling strong moral values.